Clinical characteristics and perinatal outcomes of pregnant women with Coronavirus-19 disease - İbrahim Ömeroğlu; Hakan Gölbaşı; Suzan Şahin; Şeyda Kayhan Ömeroğlu; Ceren Gölbaşı; Atalay Ekin (Perinatal Medicine Foundation, 2022)
Objective: The aim of this study was to evaluate the maternal and perinatal outcomes of COVID-19 infection during pregnancy. Methods: We performed a retrospective review of medical records of 37 pregnant women with the diagnosis of COVID-19. The clinical characteristics, laboratory results, perinatal and neonatal outcomes were analyzed. Results: The majority of cases with COVID-19 were evaluated as mild (97.3%). None of the women needed intensive care unit or invasive mechanical ventilation and mortality were not observed. The most common symptoms were fever (62.2%) and cough (40.5%). Of all the pregnancies, 5.4% ended with abortion, 2.7% with stillbirth, and 10% of the infants were hospitalized in the neonatal intensive care unit. Neonatal mortality was not observed. Conclusion: In our study, none of the pregnant women with SARS-CoV-2 infection had severe illness. Vertical transmission of SARS-CoV-2 which was possible in several studies is not observed in our patient population.